IN VITRO BEHAVIOUR OF NEW EXPERIMENTAL ADHESIVE SYSTEMS - SUCALĂ, Diana; SAROSI, Codruţa; POPA, Cătălin Ovidiu; COJOCARU, Ileana; MOLDOVAN, Marioara; MOHAN, Aurel George (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Bonding of current adhesives to dentin is usually through the formation of the interfacial hybrid layer between adhesives and dentin. Inter-tubular and intra-tubular resin infiltration leads to an increase of the quality regarding the dentinal adhesion. The aim of this study is in vitro testing of new experimental adhesives in comparison with commercial adhesive, regarding sorption and solubility as well as to investigate molecular chemical features of the adhesive/dentin interfaces. We used 4 experimental adhesives systems A1, A2, A3, A4 and IBond® (Heraeus) as reference material. Organic phase adhesive system consists of a mixture of monomers. As filler for these systems, besides hydroxyapatite, we used TiO2 nanoparticles. FTIR spectroscopy was used to investigate molecular chemical features of the adhesive/dentin interfaces. The obtained data show the main advantages and disadvantages of the tested adhesive systems. The best values of water sorption and solubility both in water and artificial saliva present A2 and A3 adhesives.